Implementation of the ABC model in a company dealing with extraction of raw materials - Bajus, Radoslav; Stašová, Lenka Hudáková (Business, Management and Economics Engineering, 2014)
ABC method is a new system for accurate product pricing, cost analysis of the causes of individual products and their optimization. The prices of products are accurately taken into account according to all relevant overhead costs in their actual context and relationships. Except of product costs, ABC method follows costs regarding customers, suppliers, distribution, transport, manufacturing, operational and security processes, management processes and other business activities. ABC method sees the company as a complex of interrelated activities and processes. ABC method represents more precise cost calculation for the product. The aim of the present article is to highlight the introduction of the ABC method to the enterprise and compare it with the traditional method. The result is to reduce costs by introducing ABC method to the enterprise.